Energy- and protein intake of surgical patients after the implementation of energy dense hospital menus. Issue 3 (June 2015) - Ingadottir, Arora R.; Hilmisdottir, Heida B.; Ramel, Alfons; Gunnarsdottir, Ingibjorg
Summary: Background and aims: Malnutrition is common among hospitalized patients and is associated with negative health consequences. Oral nutrition supplements (ONS) have been used to improve nutritional status of malnourished patients. Considering the costs and the sometimes poor acceptance of ONS, the present study investigated the effects of changing hospital food composition on patients' energy- and protein intake. Methods: One-hundred-and-six patients admitted to the Department of Cardio Thoracic Surgery at University Hospital in Iceland in 2013 were recruited. Inclusion criteria were age ≥18 years, hospital stay of ≥five days and ability to eat. In 2012 a new hospital menu was implemented and the meals contain more energy dense foods in comparison to earlier. Energy- and protein intake from the five meals provided daily were estimated using a validated plate diagram sheet on days 3–5 after surgery and compared to similar data retrieved in 2011. Results: In 2013 92 participants finished the study, data from 69 patients were available from 2011. Energy- and protein requirements were similar between years. Energy provided by meals was higher in 2013 (1711 ± 199 vs. 1946 ± 65 kcal, P < 0.001), accordingly energy intake from meals was higher in 2013 (1096 ± 340 vs. 1293 ± 386 kcal/d; P = 0.001). Protein intake from meals was not different. However, the total energy- and protein intake of patients was unchanged between 2011 (1374 ± 394 kcal; 62.1 ± 17.8 g) and 2013 (1452 ± 389 kcal; 60.2 ± 17.2 g) because the consumption of in-between meals (ONS or food brought from home) was less in the 2013 (170 ± 171 vs. 282 ± 207kcal, P < 0.001 and 13.2 ± 10.3 vs. 6.9 ± 6.5 g, P < 0.001, respectively). Conclusions: Our study shows that an increase in energy density increases energy consumed from hospital meals, however, they did not increase total energy intake due to a decrease in use of ONS and home brought food.